Predictors of Social Isolation Among Community-dwelling Older Adults in Iran - Mohammad Ali Soleimani; Maryam Mafi; Seyedeh Ameneh Motalebi; Elaheh Taghvaei (University of Social Welfare & Rehabilitation Sciences, 2021)
Objectives: Social isolation can lead to depression, reduced life expectancy, and increased death anxiety among older adults. The present study aims to determine the predictors of social isolation in community-dwelling older adults residing in Qazvin, Iran. Methods & Materials: This descriptive cross sectional study was conducted on 301 older adults in 2019 who were selected using a cluster sampling method. Data were collected using a demographic/clinical checklist, Lubben Social Network Scale, Multidimensional Scale of Perceived Social Support, World Health Organization Disability Assessment Schedule, 5-item World Health Organization Well-Being Index, and Pargament's Religious Coping Questionnaire, which were completed through face to face interview. The collected data were analyzed using multivariable regression analysis. Results: The Mean±SD age of participants was 68.63±7.31 years. Multivariate regression analysis showed that the significant predictors of social isolation were social support (β=0.333, P<0.001), disability (β=-0.137, P=0.018), and living with spouse (β=0.154, P=0.010). The social isolation was reduced by increasing social support, decreasing disability, and living with spouse. Conclusion: Given the role of social support and disability in predicting social isolation in the elderly, it seems that one of the effective factors in reducing social isolation especially in the disable older adults is establishing or strengthening supportive social networks.